2005
DOI: 10.1017/s148180350001318x
|View full text |Cite
|
Sign up to set email alerts
|

Nurse-initiated, titrated intravenous opioid analgesia reduces time to analgesia for selected painful conditions

Abstract: Objectives: Traditionally, patients have to wait until assessed by a physician for opioid analgesia to be administered, which contributes to delays to analgesia. Western Hospital developed a protocol enabling nurses to initiate opioid analgesia prior to medical assessment for selected conditions. The aim of this study was to determine the impact of this protocol on time to first opioid dose in patients presenting to the emergency department (ED) with renal or biliary colic. Methods: This was an explicit medica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
33
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(33 citation statements)
references
References 20 publications
0
33
0
Order By: Relevance
“…While these tests should theoretically not delay analgesia, patients who require more diagnostic evaluation have been shown to wait longer for their analgesia. 28 Similarly, there was no assessment made of the basis for the lower triage scores given to the women or whether these were born out by differences of severity in the final diagnosis. Arguing against this hypothesis in the current study is the fact that while the triage class is the basis for the urgency with which patients are brought back to the treatment area, the ED physician who determines the need for analgesia may not have this information.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While these tests should theoretically not delay analgesia, patients who require more diagnostic evaluation have been shown to wait longer for their analgesia. 28 Similarly, there was no assessment made of the basis for the lower triage scores given to the women or whether these were born out by differences of severity in the final diagnosis. Arguing against this hypothesis in the current study is the fact that while the triage class is the basis for the urgency with which patients are brought back to the treatment area, the ED physician who determines the need for analgesia may not have this information.…”
Section: Discussionmentioning
confidence: 99%
“…29 Similarly, nurse-initiated analgesia for specific painful conditions has been shown to decrease time to analgesia by 50% compared to physician-initiated analgesia. 28 Although not specifically studied in our study, it is likely that determination of pregnancy status at triage and the placement of female patients in rooms, not hallways, in the treatment area would decrease patients' wait times before receiving analgesia. Similarly, triagedriven analgesic administration for patients with moderate pain (e.g., for pain scores >5) may further decrease treatment delays and also ensure that all patients receive analgesia.…”
Section: Policy Implicationsmentioning
confidence: 94%
“…38 Kelly and colleagues showed that by enabling nurses to initiate opioid analgesia prior to medical assessment by physicians for selected painful conditions, the median time to fi rst analgesic dose decreased from 57 minutes to 31 minutes. 39 In 2007, Bijur and colleagues showed that intravenous morphine at 0.1 mg/kg was not effective for controlling severe acute pain in a majority of patients. The results showed that of 119 patients, 67% of the patients who received intravenous morphine at 0.1 mg/kg reported a less than 50% decrease in pain.…”
Section: Opiophobia In Emergency Departmentmentioning
confidence: 99%
“…7 New frontiers, such as nurse-initiated analgesics while the patient is in triage or with the use of delegated acts, are growing rapidly. [8][9][10][11] Patients in many EDs are now routinely provided topical or local anesthesia for simple (yet painful)…”
mentioning
confidence: 99%
“…Perhaps most importantly, the absence of such signs does not exclude the experience of pain. [6][7][8][9][10] The very idea of quantifying pain is somewhat controversial. Germaine to the debate is a nineteenth century contention made by William Thomson (Lord Kelvin) that worthy knowledge should be quantifiable in the form of…”
mentioning
confidence: 99%